Generous gestures: What is the point of G8 debt cancellation? - Andrea Schmitz (Stiftung Wissenschaft und Politik (SWP), 2005)
During their meeting at Gleneagles in Scotland, the heads of government of the G8 countries confirmed the decision made by their finance ministers in June to cancel the debts to multilateral financial institutions of eighteen developing countries, most of them in sub-Saharan Africa, and to substantially increase development aid. The cause was championed above all by Britain, which currently holds the G8 presidency and has put the fight against poverty in Africa at the center of a public campaign. The debt cancellation triggered off a debate about the effectiveness of development aid and revealed considerable differences between US and European policy. This debate exposes a structural dilemma at the root of the development business which significantly limits the possibilities of external intervention. (SWP Comments / SWP)
Keywords: 320